dsgrin
dsgrin
03-11-2016
Mathematics
contestada
Find f(3) of f(x) = -5x + 9.
Respuesta :
Аноним
Аноним
03-11-2016
Hello! To solve this equation, you'll plug 3 into x.
f(3)= -5(3) + 9
f(3)= -15 +9
f(3) = -6
Answer Link
ericosouki
ericosouki
03-11-2016
Hello,
Shall we begin?
f(x) = -5x + 9
f(3) = - 5 * 3 + 9
f(3) = - 15 + 9
f(3) = - 6
Answers: f(3) = - 6
Answer Link
VER TODAS LAS RESPUESTAS ( 72+ )
Otras preguntas
In a circle of any size, what ratio does pi represent?
US intervention in Iran in the 1950s
find the least common multiple (lcm) of 28 and 7
The skateboards that belong to the guys which shows how to correctly rewrite this phrase using an apostrophe? a. the guys' skateboards b. the guys's skateboar
which of the following is a simple sugar? a) lactase b) glucose c) lactose d) sucrose
Which of these kinds of tissues stores fat? adipose cartilage epithelium fibrous connective user: when you move your arm to use your computer mouse, which of th
What is the period of f(x)=sin(x)
The viral infection Hepatitis A can be most effectively controlled if?
why does the function of the hormone oxytocin in the progression of labor during childbirth illustrate a positive feedback mechanism
why are enzymes important? a) enzymes are complete proteins essential for good health. b) enzymes break down proteins for use in the body. c) enzymes carry oxyg